A suite of wildlife crossing structures facilitates mammal movement across tropical forest fragments in a city - Li Si Tay; Ruisheng Choo; Max D. Y. Khoo; Eunice Kong; Yi Xiang Chan; Wivian H. Y. Neo; Sebastian Ow; Yuet Hsin Toh; Han Ling; Malcolm C. K. Soh; Benjamin P. Y.‐H. Lee; Adrian H. B. Loo; et al. (Ecosphere)
Abstract Wildlife crossing structures and road calming measures are frequently implemented to improve habitat connectivity and mitigate the risks of wildlife–vehicle collisions on roads. Although Southeast Asia is a known biodiversity hotspot, majority of studies assessing effectiveness of such structures were conducted outside the region. Existing studies also tended to be non‐comparative and focused on crossing structures in silo. We addressed this gap by simultaneously surveying and comparing the usage frequency of mammals across three crossing types—culverts, roads and rope bridges—along a road surrounded by forests in Singapore. This allowed us to evaluate the preferences of mammals, assess usage patterns and investigate factors influencing the use of different crossing types. Using camera traps and closed‐circuit televisions, we documented 1133 independent crossing events across a 9‐month study period from March to November 2021. Fourteen mammal species were detected across all crossing types, with wild boar (Sus scrofa) being the most prevalent species (68.2%). Locally critically endangered species such as the Malayan porcupine (Hystrix brachyura), Sunda pangolin (Manis javanica), and Raffles' banded langur (Presbytis femoralis femoralis) were also recorded to use culverts, roads, and rope bridges for crossings, respectively. Although many species used multiple crossing types, most species had a preferred crossing method. Between culverts and roads, factors that influenced crossing preferences included group size for wild boars and time of day and presence of fences for other mammals. Even though such culverts were intended for drainage, they were still widely used by mammals. Overall, all three crossing methods were crucial in facilitating the movement of animals between habitats. Thus, a variety of infrastructure and measures to accommodate the diversity of wildlife moving across forest patches in a fragmented landscape is recommended.